Delayed access to care and late presentations in children during the COVID‐19 pandemic New Zealand‐wide lockdown: A New Zealand Paediatric Surveillance Unit study. (18th May 2021) - Duncanson, Mavis; Wheeler, Benjamin J; Jelleyman, Timothy; Dalziel, Stuart R; McIntyre, Peter
Abstract : Aim: Describe paediatricians' experience of adverse health outcomes for children during the New Zealand‐wide level 4 lockdown in response to the COVID‐19 pandemic. Methods: Weekly national survey of paediatricians with an open‐ended questionnaire. Results: During the 6‐week study survey period, the New Zealand Paediatric Surveillance Unit received 33 reports about 55 instances where paediatricians believed care may have been compromised, about half (56%) relating to infants aged from birth to 6 weeks. Compromised care was for acute presentations in 75%, acute complications of a chronic illness in 14%, with 11% for chronic conditions. Paediatricians reported the outcome as moderately severe (short‐term morbidity, increased length of stay, higher level of care) in 38 cases (69%) and in a further 4 (7%) as severe (potential to be life‐threatening or result in permanent disability). Conclusion: Despite clear messaging, hospital avoidance and reduced access to primary and secondary care were associated with significant potential harm for children in New Zealand during a strict lockdown, with newborn infants disproportionately affected. During the implementation of interventions to eliminate community transmission of COVID‐19, New Zealand paediatricians note the importance of face‐to‐face post‐natal visits for newborns and primary care services for children with acute illness, to avoid preventable harm.